Pelaksanaan Perjanjian Bagi Hasil Pohon Aren terhadap Petani dan Pemilik di Desa Juhar Ginting Sada Nioga - Pinem, Jaya Prana; Barus, Utary Maharani; Isnaini, Isnaini (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
This study discusses the implementation of palm tree production sharing agreements; what are the legal consequences if one of the parties defaults on the palm tree profit sharing agreement and is there legal certainty for the implementation of the palm tree production sharing agreement in Juhar Ginting Sada Nioga Village based on "Customary Law" and "Law No. 6 of 1960â€ concerning Production Sharing Agreements. This research is descriptive analytical. The collected data were analyzed using empirical juridical methods. This study found (1) the implementation of production sharing agreements is carried out by means of unwritten or oral agreements, but the implementation is carried out according to the customs that exist in the community. The profit sharing that is carried out is not contrary to Law no. 2 of 1960, but in terms of the form and duration of the production sharing agreement it is not in accordance with the provisions stipulated in the law. (2) The legal consequences arising from defaults that occur in the implementation of the agreement for planting palm tree yields, usually only according to local customary law, namely compensation and cancellation of the production sharing agreement. (3) The principle of legal certainty regarding profit-sharing agreements has not been implemented, this is due to the lack of public knowledge about the law of production-sharing agreements so that the implementers of the agreement only make agreements based on local customs and habits.